The State of Civil-Military Relations Education: Falling Short? - Weiss, Cornelia (Hemisferio - Revista del Colegio Interamericano de Defensa, 2020)
This paper addresses the state of civil-military relations (CMR) education by addressing whether CMR is taught at military and civilian institutions, the gap between CMR scholarship produced and CMR materials studied, and the ability to create better CMR syllabi (by ending a practice of excluding female-authored works in CMR syllabi).